Complete genome sequence of the gliding freshwater bacterium Fluviicola taffensis type strain (RW262T) - Woyke, T.; Chertkov, Olga; Lapidus, A.; Nolan, Matt; Lucas, S.; Mwirichia, Romano K.; et al. (My University, 2011)
Fluviicola taffensis O'Sullivan et al. 2005 belongs to the monotypic genus Fluviicola within the family Cryomorphaceae. The species is of interest because of its isolated phylogenetic lo-cation in the genome-sequenced fraction of the tree of life. Strain RW262T forms a monophy-letic lineage with uncultivated bacteria represented in freshwater 16S rRNA gene libraries. A similar phylogenetic differentiation occurs between freshwater and marine bacteria in the family Flavobacteriaceae, a sister family to Cryomorphaceae. Most remarkable is the inability of this freshwater bacterium to grow in the presence of Na+ ions. All other genera in the fami-ly Cryomorphaceae are from marine habitats and have an absolute requirement for Na+ ions or natural sea water. F. taffensis is the first member of the family Cryomorphaceae with a completely sequenced and publicly available genome. The 4,633,577 bp long genome with its 4,082 protein-coding and 49 RNA genes is a part of the Genomic Encyclopedia of Bacteria and Archaea project.
DOI:10.4056/sigs.2124912
Keywords: strictly anaerobic; motile by gliding; Gram-negative; flexirubin-synthesizing; meso-philic; chemoorganotrophic; Cryomorphaceae; GEBA